PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS III SD INPRES ANTANG: - Ashar, Nurfadilah; Syam, Nur; Rahmawati, Rahmawati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to determine the effect of the visual media-assisted discovery learning model on increasing thematic learning outcomes of third-grade students at SD Inpres Antang 1 and to find out the differences in learning motivation for students after and after following the visual media-assisted discovery learning model on thematic learning of third-grade students at SD Inpres Antang 1. The method used was experimentation with the type of research being pre-experimental design in the form of one group pretest-posttest design and the data collection technique used was observation, testing and documentation. Based on the results of the study, it was shown that the visual media-assisted discovery learning model had a positive and significant effect on improving the thematic learning outcomes of third grade students at SD Inpres Antang 1. This learning model can help students understand learning material better. The use of visual media can also help students visualize concepts that are difficult to understand and this research provides empirical evidence that supports the positive impact of the Discovery Learning Model on the thematic learning outcomes of third grade students. By actively engaging in the learning process, exploring new concepts, and solving problems, students show increased intrinsic learning outcomes, self-efficacy, and overall engagement. These findings emphasize the importance of applying a student-centred approach, such as the Discovery Learning Model, to create a motivating learning environment.